Educational Character Values in Seloko Custom Utterances of Jambi Malay Society - Rahima, A (KnE Social Sciences, 2018)
The objective of this research is to describe traditional utterances in the Seloko customs of Jambi Malay society. This research is also intended to describe the educational character values in the Seloko customs of Jambi Malay society. The results of the research show that some educational values are found in the Seloko customs of Jambi Malay society: (1) the educational values related religion faith, which contain religious matters, such as obedience to religious law; (2) the educational character values that are related to the self, consisting of honesty, responsibility, discipline, and hard work; (3) the educational character values that are related to society, consisting of self-responsibility, obedience to social rules, politeness, loyalty, and caring; (4) the educational character values that are related to the environment, consisting of being aware of the environment and an anti-violent attitude. Keywords: educational character values, Seloko custom, utterances